2020
DOI: 10.1177/0047287520946103
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Scale to Measure Tourist Perceived Safety

Abstract: Safety for tourists at places visited is essential to their enjoyment and experiences, as well as a determinant of destination success. Yet, little attention has been paid to the conceptualization and scale development for tourist perceived safety at destinations (TPSD). The primary purpose of this research was to identify the dimensions of TPSD and develop a scale for measuring it based on safety system theory. A three-stage study in a mixed-method design was conducted to develop and validate TPSD. Stage 1 id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 79 publications
1
55
0
Order By: Relevance
“…There is broad scholarly consensus that information-search is among the most effective strategies used by individuals to reduce their uncertainty in the decision-making process and attain a sense of security prior to travel (Jonas and Mansfeld, 2017; Liu and Hu, 2021). As consumers form their perceptions of safety out of the information they obtain, their perceived safety depends on how they evaluate that information (Xie et al , 2021) and in this regard there are studies empirically demonstrating the effect of information on tourist perceived safety (Liu-Lastres et al , 2019; Liu et al , 2016a; Xie et al , 2021; Zou and Meng, 2020). It is for this reason that information is of exceptional value for tourism during times of crisis (Liu-Lastres et al , 2019) as a crucial factor that can influence consumers’ perceptions of the severity of the threat (Liu et al , 2016a).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…There is broad scholarly consensus that information-search is among the most effective strategies used by individuals to reduce their uncertainty in the decision-making process and attain a sense of security prior to travel (Jonas and Mansfeld, 2017; Liu and Hu, 2021). As consumers form their perceptions of safety out of the information they obtain, their perceived safety depends on how they evaluate that information (Xie et al , 2021) and in this regard there are studies empirically demonstrating the effect of information on tourist perceived safety (Liu-Lastres et al , 2019; Liu et al , 2016a; Xie et al , 2021; Zou and Meng, 2020). It is for this reason that information is of exceptional value for tourism during times of crisis (Liu-Lastres et al , 2019) as a crucial factor that can influence consumers’ perceptions of the severity of the threat (Liu et al , 2016a).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Perceived safety in the tourism context refers to the traveler’s sense of being free from danger or physical or mental stress due to the interference of external forces (Xie et al , 2021). The safety perceived by a consumer prior to making a trip is a subjective impression that relies on their assessment of the information available to them, coupled with their past experiences (Seabra et al , 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…It is almost certain that perceived risk factors that influence a person's decision to travel significantly affect their satisfaction, and willingness to return, i.e., tourists' behavioral intentions (Fourie, et al, 2020;Xie, Zhang, & Morrison, 2021). It is reported that the intention to revisit and recommend is significantly affected by perceived risk factors, similar to the concept of satisfaction.…”
Section: Recommendation and Revisit Intentionsmentioning
confidence: 99%